Entrepreneurship Practices of Higher Education Institutions in Region IV-A, Philippines - Jesus P Briones; Joanna Paula E Verano; Robert G Uy; Erwinson B Atanacio; Rey Fernan G Refozar; Zosimo D Maglangit Jr (Research Synergy Foundation, 2023)
This study investigated the entrepreneurship practices (EPs) of higher education institutions (HEIs) in Region IV-A, Philippines. This descriptive-quantitative research used an adapted questionnaire which was based on the HEInnovate framework for entrepreneurial universities covering the eight dimensions. The data were gathered from 137 business educators who were affiliated with HEIs located in the five provinces of Region IV-A. Findings revealed that HEIs in the region are in their transformative stage of becoming entrepreneurial universities subject to improvements in five HEInnovate framework dimensions for entrepreneurial universities. Moreover, the study also proved that profile indicators utilized in the study are not factors for the variation of EPs among the subject-HEIs. The roadmap strategy proposed by the researchers is recommended to serve as a guide for the subject-HEIs in drawing up their plans and programs in their journey to become entrepreneurial universities.